2017
DOI: 10.5957/josr.61.2.160046
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of Ride Control Algorithms for High-Speed Catamarans Part 2: Mitigation of Wave Impact Loads

Abstract: High-speed craft frequently experience large wave impact loads due to their large motions and accelerations. One solution to reduce the severity of motion and impact loadings is the installation of ride control systems. Part 1 of this study investigates the influence of control algorithms on the motions of a 112 m high-speed catamaran using a 2.5 m model fitted with a ride control system. The present study extends this to investigate the influence of control algorithms on the loads and internal forces acting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 6 publications
3
16
0
Order By: Relevance
“…Linear gains ensured that control deflections only just reached maximum possible amplitudes whereas nonlinear gains always employed maximum up or down control forces subject to the constraint of the control surface slew rates (approximately 300°/s) between these conditions. Whilst the intent of the model RCS feedback settings was to produce motion damping, significant phase shifts in the small model scale feedback system resulted in control actions which effectively included additional motion stiffness effects [7,8]. As will be seen this was a beneficial aspect of the model RCS system.…”
Section: Ride Control Algorithmsmentioning
confidence: 97%
See 2 more Smart Citations
“…Linear gains ensured that control deflections only just reached maximum possible amplitudes whereas nonlinear gains always employed maximum up or down control forces subject to the constraint of the control surface slew rates (approximately 300°/s) between these conditions. Whilst the intent of the model RCS feedback settings was to produce motion damping, significant phase shifts in the small model scale feedback system resulted in control actions which effectively included additional motion stiffness effects [7,8]. As will be seen this was a beneficial aspect of the model RCS system.…”
Section: Ride Control Algorithmsmentioning
confidence: 97%
“…A comprehensive literature review of RCS has been previously presented by the authors [7,8]. Although some studies on ship motions and motion control systems have been undertaken by numerical computations, experimental investigations and full-scale sea trials , there is still limited knowledge on the mechanisms of the whole motion control system and to date there has been little published work on their optimum mode of operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of relevant studies for motion and wet-deck slamming in catamarans can be found in [27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Several model experiments in irregular [17,18,30] and regular waves [1,14,16], including systematic tests on CB designs [5,6,31] and ride control performance [32,33] have been conducted over the past decade to identify slamming loads and motions of WPCs in various operational conditions. However, very few have measured pressure, especially in combination with slam loads.…”
Section: Introductionmentioning
confidence: 99%